Performance of accredited social health activists for maternal health component of their job responsibility in a rural block of Sonipat district of Haryana: a cross-sectional study - Singhal, Parul; Majra, J. P.; Jha, S. K. (International Journal Of Community Medicine And Public Health, 2020)
Background: Accredited social health activists (ASHAs) play an inevitable role in universal healthcare provision. Improving maternal health has been essential element for achieving health for all. ASHAs and their activity are considered as the one of the key components of national health mission. This study was conducted to assess the performance of ASHAs for maternal health component of their job responsibility in rural block of juan, Sonipat district of Haryana. Methods: This descriptive cross-sectional study was conducted among all ASHAs in rural block of juan, Sonepat district of Haryana between April 2018 to March 2019. Pretested semi-structured interview schedule was used to collect the data. The activity wise as well as cumulative incentive received by the ASHAs for the previous six months was used for study purpose. Data was analyzed by using SPSS version 22. Results: All the ASHAs prepared the monthly list of pregnant women. Almost all (97.9%) ASHAs registered the pregnant women up to 12 weeks and all of three antenatal check-ups within concerned trimester and 95.9% ASHAs involved in HBPNC cases. Total incentive earned by ASHAs in maternal health components was ranging from Rs. 950-12150, average incentive earned was Rs. 4982 during the period of six month. Conclusions: There is a huge variation in the incentive earned by in maternal health component by the ASHAs. Further more than half of the ASHAs have not accompanied the pregnant women to the institutional delivery.